Sistemas de estabilização em polipropileno submetidos à radiação UV-C - Basaglia, Marcos Vinícius (Universidade Federal de São Carlos, 2023)
UV-C radiation (200 - 280 nm) is a range of the electromagnetic spectrum with increasing and satisfactory studies as a method of disinfection against microorganisms, however, it is little studied in terms of degradation of polymeric materials. This range of radiation is more energetic compared to UV-A and UV-B radiation, presenting potential to break chemical bonds that would be stable in these two ranges. In this sense, the degradative effects caused to polypropylene subjected to UV-C radiation for 24, 48, and 96 hours in the presence of different stabilization systems containing phenolic stabilizers (Irganox 1010), hydroxylamine (Irgastab FS 042), phosphite (Irgafos 168), and UV absorber (Tinuvin 1577) were analyzed. The formulations were processed in an internal mixer and shaped into films with 180 μm thickness. As the processing step can influence the degradative effects of subsequent steps, these were also analyzed for the same additive sets. Degradation levels were analyzed in terms of rheology, molecular weight, Fourier-transform infrared spectroscopy (FTIR), mechanical properties, contact angle, and scanning electron microscopy (SEM). For processing, Irganox 1010 proved to be more efficient in all process conditions used, while Irgastab FS 042 was unable to provide stability at high temperatures (240 ºC) and oxidative atmosphere, which was improved using lower temperatures and inert atmosphere. After UV-C irradiation, FTIR and rheology analyses showed that the use of hydroxylamine is more efficient in initial exposure times, while the phenolic class is more effective for longer times. After 96 hours, polypropylene begins to exhibit brittle behavior, which can be avoided with the joint use of UV absorber and phenol or hydroxylamine-based stabilizers, suggesting a synergistic effect between additives.
Stabilization systems in polypropylene exposed to UV-C radiation
Keywords: Degradação; Foto-oxidação; Radiação UV-C; Sistemas de estabilização; Hidroxilamina; Polipropileno; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA